Coaching as a Strategy for Learning Community Development to Enhance Teachers’ Pedagogical Competence: A Case Study in a Elementary School - Suyun Whindari; Widya Kusumaningsih; Harto Nuroso (FKIP - Universitas Riau, 2026)
Continuous professional development is essential to improve teachers’ competence and respond to educational transformation. This study aims to analyze the implementation of coaching as a strategy for developing a learning community (komunitas belajar) to enhance teachers’ pedagogical competence at SD Negeri Candirejo 02 Ungaran Barat. A qualitative case study approach was employed using interviews, observations, and documentation involving the principal, teachers, and learning community coordinators. Data were analyzed through interactive thematic analysis. The findings show that coaching strengthened teacher professional development through collaborative discussions, reflective practice, peer feedback, and classroom observation. Teachers’ pedagogical competence improved in differentiated lesson planning, student-centered learning, instructional material development, formative assessment, classroom management, and reflective teaching. The principal played a key role in sustaining coaching activities, although implementation was constrained by limited time, administrative workload, and differences in teacher readiness. The novelty of this study is a coaching based learning community model integrating instructional leadership, collaborative professional learning, and reflective coaching as a sustainable educational management strategy. This study concludes that coaching-based learning communities effectively strengthen teachers’ pedagogical competence and foster sustainable professional learning in elementary schools.